I was truly addicted to sugar: A consumer-focused classification system of behaviour change strategies for sugar reduction. (1st January 2020) - Rodda, Simone N.; Booth, Natalia; Brittain, Matthew; McKean, Jessica; Thornley, Simon
Abstract: The reduction of free sugars has been identified as a priority issue internationally. A range of public health initiatives have been recommended, including the provision of information and support for sugar reduction. To inform these approaches, it is important to know what people actually do in real world settings to reduce their consumption. This study documents and defines the range of consumer-based behaviour change strategies for sugar reduction. A total of 1145 strategies were extracted from 47 internet sources (i.e., consumer, popular and professional). Using a pragmatic content analysis, hundreds of strategies were organized into 25 discrete categories of strategies. Categories were grouped into the Rubicon Model of Action Phases and classified as pre-decisional (i.e., decisional balance, feedback, realisation, seek knowledge and information), post-decisional (i.e., action planning, coping planning, set goal intention, sugar guidelines) and actional phase. Actional strategies were the most prolific and included avoidance, consumption control, consumption planning, environmental restructuring, healthy eating focus, maintain readiness, professional support, refocusing, self-monitoring, social support, substance substitution, tapering, address underlying issues, urge management, well-being and withdrawal management. There was one post-actional strategy which was associated with self-evaluation (i.e., reviewing a change attempt in order to plan for the future). Four categories of strategies differed according to the source. Substance substitution was substantially less frequently discussed by consumers than professionals and few professional sites acknowledged or advised strategies to manage the struggle of maintaining readiness following a change attempt. Hundreds of individual strategies are discussed or promoted in online settings, and more information is needed on the effectiveness of these self-initiated approaches.